Best practices for your website . eNewsletter a primer - McDonald, Loren; Stanford Video Media Group; Kantola Productions (Mill Valley, CA : Kantola Productions [distributors] : Stanford Video [productions], 2003)
Loren McDonald, founder and president of interation, details the major processes for creating, delivering and maintaining a successful eNewsletter
Created by the developers of the Stanford Professional Publishing Course
Executive producer, Steve Kantola ; producer, Catherine O' brien; editor, Melissa Peabody ; graphics, Paul Stelhe ; production services, New Dawn Studios
Narrator : Richard Gephardt
Keywords: Electronic newsletter; Web sites -- Design; Internet marketing